CARF is a multi-module regulator of cell proliferation and a molecular bridge between cellular senescence and carcinogenesis. (September 2017) - Wadhwa, Renu; Kalra, Rajkumar Singh; Kaul, Sunil C.
Highlights: CARF (Collaborator of ARF) was first identified as an ARF-interacting protein that stabilizes p53-tumor suppressor protein. It acts as a transcriptional repressor of HDM2 that exerts a negative feedback on p53 by its proteasomal-mediated degradation. CARF-driven control over p53-HDM2-p21 WAF1 axis was shown to regulate cell proliferative fates. Whereas cells with CARF-overexpression show growth arrest, its superexpression enhances proliferation. In the present review, we discuss how threshold level of CARF determines the fate of cells to either senescence or malignant transformation. Abstract: CARF (Collaborator of ARF) was first identified as an ARF (Alternative Reading Frame, p14ARF)-interacting protein in a yeast two-hybrid interactive screening. Subsequently, it was shown to stabilize the p53-tumor suppressor protein in an ARF-dependent or −independent manner. It acts as a transcriptional repressor of HDM2 that exerts a negative feedback on p53 by its proteasomal-mediated degradation. CARF-driven control over p53-HDM2-p21 WAF1 axis was shown to regulate cell proliferative fates. Cells with CARF-overexpression (CARF-OE) and superexpression (CARF-SE) showed growth arrest and pro-proliferative phenotypes, respectively. On the other hand, apoptosis was triggered in CARF-compromised cells. In the present review, we provide a comprehensive current understanding into the molecular mechanisms of CARF functions in regulation of DNA damage response, cell cycle checkpoints, cell survival and death signaling pathways. We discuss how thresh-hold of CARF level determines fate of cells to senescence and malignant transformation.